2017
DOI: 10.1039/c6cp08031f
|View full text |Cite
|
Sign up to set email alerts
|

The phase and interfacial properties of azeotropic refrigerants: the prediction of aneotropes from molecular theory

Abstract: The use of hydrofluorocarbons (HFCs) as alternative non-ozone depleting refrigerants for chlorofluorocarbons (CFCs) and hydrochlorofluorocarbons (HCFCs) has grown during the last couple of decades. Owing to their considerable global warming potential, a global deal has been reached recently to limit the production and consumption of HFCs. For rational design of new refrigerants that are environmentally friendlier, the thermodynamics of current ones need to be well understood first. In this work, we examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 81 publications
1
26
0
Order By: Relevance
“…The parameter c ij for the components i and j , or simply c , is known as the influence parameter . In this work, the influence parameter required by the theory was fitted to pure component surface tension data and then used to predict the interfacial properties of refrigerant blends; their values are provided in Table , where the values of c used for the other refrigerants as taken from published works in a transferable manner are also provided.…”
Section: Molecular Modelingmentioning
confidence: 77%
See 4 more Smart Citations
“…The parameter c ij for the components i and j , or simply c , is known as the influence parameter . In this work, the influence parameter required by the theory was fitted to pure component surface tension data and then used to predict the interfacial properties of refrigerant blends; their values are provided in Table , where the values of c used for the other refrigerants as taken from published works in a transferable manner are also provided.…”
Section: Molecular Modelingmentioning
confidence: 77%
“…In a previous publication, it was shown that 1,1‐difluoroethane (HFC‐152a) and 1,1,1,2‐tetrafluoroethane (HFC‐134a) share great similarities in terms of their thermophysical properties. The same applies for 1,1,1‐trifluoroethane (HFC‐143a) and 1,1,1,2,2‐pentafluoroethane (HFC‐125).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations